Development and Field Testing of a Narrative-Centered Digital Game for English Comprehension (International Conference on Computers in Education, 2020)
This paper describes the development and field testing of Learning Likha: Rangers to the Rescue, a narrative-centered, mobile-based digital game for practicing English comprehension. Twenty-seven (27) student participants from Grades 4, 5, and 6 were invited to play the game and answer a comprehension test to determine their level of understanding of the game’s contents. Self-report questionnaires were also used to assess the extent to which they enjoyed playing the game. Three (3) teachers were likewise invited for a focus group discussion (FGD) to gather their insights about the game and how they may use it in their classes. Student’s self-reported feedback indicated they found the game fun, interesting, and sufficiently challenging. Post-test comprehension scores were generally good. Younger participants scored lower than their older peers but the differences were found to be not significant. Teachers indicated the game has the potential to be used as a supplement for their classes and that their students would enjoy playing it.